JOURNALISTIC WRITING: A FUNCTIONAL VIEW OF NOUN PHRASE IN PAKISTANI ENGLISH NEWSPAPERS - Irfan-Ul-Wahab; Akhtar Aziz (International Journal of Contemporary Issues in Social Sciences, 2024)
Language is a common tool for communication among human beings worldwide. That is why it is defined as choice in context which means that whenever one wants to convey to other, one makes choice of linguistic codes or forms in view of the situation of the communication (context), purpose or goal of communication, and the target receiver(s). These linguistic forms utilised in communication perform different functions; these linguistic forms may lead us to three types of functions which are Grammatical/Syntactic function, Semantic function, and Pragmatic function. Semantic, and Pragmatic functions may be summed up into Semiotic function; these functions operate in connection to meaning of the clause, or the utterance while grammatical functions operate in connection to syntactic structure in which those linguistic forms are used. Semiotic functions are expressed by linguistic forms in the shape of language codes while these linguistic forms are connected to their semiotic functions through grammatical functions. The choice of linguistic forms generate variation in the real life instance of language use; the very variation of language depends on goal, topic, context, register, genre, syntactic function, receiver, and the substrate languages of the users. Syntactic bits like phrases or groups express these variations in their linguistic forms which may be analysed by language studies for interpretation. In this regard, nominal group or noun phrase is considered as structural parallel of clause in certain features. In addition, noun phrase is considered more important communicatively from other phrases by linguists as it is visible in the child language, motherese. Similarly, nominal group is a vital form in the language of newspaper which is generally termed as journalese. Daily papers express variation in their use of nominal groups due to the facts that these papers cater for different purposes, and receivers. Likewise, the register of newspaper show variations at three levels: at the level of different newspapers circulated by different news agencies, at the level of different sections of the newspaper because different sections of newspapers belong to different genres of communication, and at the level of geography or society because a register at local, national, and international level may display linguistic variation. The present study describes these variations in the linguistic forms of the nominal group in the English language newspaper utilised daily in the major cities like capital, and provincial capitals of Pakistan. The linguistic forms of the nominal group are analysed in reference to their grammatical or syntactic functions in the five sections of the five well established English newspaper of Pakistan quantitatively.